New Insights Into Cancer Chronotherapies - Zhou, Jingxuan; Wang, Jiechen; Zhang, Xiaozhao; Tang, Qingming (Frontiers in Pharmacology, 2021)
Circadian clocks participate in the coordination of various metabolic and biological activities to maintain homeostasis. It has been confirmed that disturbances of circadian rhythms and cancers are closely linked. Clock genes have their own expression characters in different tumors, which accelerate the development and progression of tumors. In addition, tumor tissues have varying biological behaviors compared with normal tissues due to the resets of rhythms. At present, chronotherapies are widely studied to treat for cancers in consideration of circadian rhythms, with high efficacy as well as mild toxicity. And with a view to optimal medication regimen, it is crucial to focus on personalized biomarkers for personal precision chronotherapies. In this review, the connection between circadian clocks and cancers, researches and applications within chronotherapies in cancers, and personalized biomarkers for precision chronotherapies are deeply discussed based on the results obtained by our research group and other studies, which aims to account for the importance of circadian clocks in cancers and provide evidence for more effective clinical treatments of tumors.